Mineral‐Filled Fractures as Indicators of Multigenerational Fluid Flow in the Pahrump Hills Member of the Murray Formation, Gale Crater, Mars. Issue 2 (23rd February 2019) - Kronyak, R. E.; Kah, L. C.; Edgett, K. S.; VanBommel, S. J.; Thompson, L. M.; Wiens, R. C.; Sun, V. Z.; Nachon, M.
Abstract: Mineral‐filled fractures (veins) are valuable indicators of deformation and fluid flow within a sedimentary package. Information obtained from vein morphology, texture, and chemistry may elucidate the sequence and nature of postdepositional fluid events. Additional information from vein patterns and interactions between veins and host rock provides insight into fracture formation mechanism(s). The widespread occurrence of veins and other diagenetic features in the sedimentary rock record preserved in Gale crater, Mars, indicates that postdepositional fluids were regionally active considerably later in time than the primary fluviolacustrine environments responsible for the deposition of Mount Sharp strata. Here we report a suite of veins within the Murray formation at the Pahrump Hills locality that were investigated using the scientific payload of the Mars Science Laboratory Curiosity rover. Based on an analysis of vein color, morphology, and texture, and corroborated by vein chemistry, we interpret three distinct vein types at Pahrump Hills: gray veins, white veins, and dark‐toned veins. These veins represent distinct, separate episodes of postdepositional fluid flow, suggesting a protracted history of fluid stability in Gale crater. Additionally, we utilize vein patterns across multiple lithologies at the Pahrump Hills field site to suggest hydrofracture as the primary mechanism of fracture formation. Key Points: Mineral‐filled fractures (veins) are identified and characterized at the Pahrump Hills locality of the Murray formation, Gale crater, Mars Morphological and chemical data on veins are used to infer multiple episodes of postdepositional fluid flow and hydrofracturing of rocks Implications for prolonged stability of depositional and diagenetic fluids in Gale crater are discussed